Centrality dependence of inclusive J/ψ production in p-Pb collisions at √sNN=5.02 TeV - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Fleck, Martin; Glässel, Peter; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Journal of high energy physics, 2015)
We present a measurement of inclusive J/ψ production in p-Pb collisions at √sNN = 5.02 $$TeV as a function of the centrality of the collision, as estimated from the energy deposited in the Zero Degree Calorimeters. The measurement is performed with the ALICE detector down to zero transverse momentum, pT, in the backward (−4.46 < ycms < −2.96) and forward (2.03 < ycms < 3.53) rapidity intervals in the dimuon decay channel and in the mid-rapidity region (−1.37 < ycms < 0.43) in the dielectron decay channel. The backward and forward rapidity intervals correspond to the Pb-going and p-going direction, respectively. The pT-differential J/ψ production cross section at backward and forward rapidity is measured for several centrality classes, together with the corresponding average pT and pT2 values. The nuclear modification factor is presented as a function of centrality for the three rapidity intervals, and as a function of pT for several centrality classes at backward and forward rapidity. At mid- and forward rapidity, the J/ψ yield is suppressed up to 40% compared to that in pp interactions scaled by the number of binary collisions. The degree of suppression increases towards central p-Pb collisions at forward rapidity, and with decreasing pT of the J/ψ. At backward rapidity, the nuclear modification factor is compatible with unity within the total uncertainties, with an increasing trend from peripheral to central p-Pb collisions.
*The ALICE collaboration: J. Adam, V. Anguelov, O. Busch, M. Fleck, P. Glaessel, J. Klein, M.L. Knichel, L. Leardini, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 974 weitere Personen]
Gesehen am 21.07.2021
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt